Iron metabolism and hepcidin concentration in teenagers before and after exercise in relation to the HFE gene status - BARBARA KACZOROWSKA-HAĆ; MARCIN ŁUSZCZYK; JĘDRZEJ ANTOSIEWCZ; JAN JACEK KACZOR (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2019)
Background: ‪The aim of the study was to compare the influence of exercise on iron metabolism and hepcidin concentration between carriers of His63Asp mutation (H63D polymorphism) and wild type HFE gene males. Iron is an essential micronutrient required for various biological processes. Systemic iron homeostasis is maintained in a hormone-like negative feedback mechanism by the 25-amino acid peptide hepcidin. Hepcidin controls duodenal iron absorption and iron recycling from senescent erythrocytes using tissue macrophages through the down-regulation of the sole known iron cell exporter, ferroportin-1. Exercise may induce an inflammatory response that leads to changes in iron metabolism. Material and methods: ‪ Iron, ferritin, hepcidin concentration and transferrin saturation were measured in carriers of His63Asp mutation of HFE and wild type teenagers before and after cycle ergometer exercise. Results: ‪His63Asp carriers had higher basal hepcidin concentration than wild type probands (p < 0.05). Interestingly, the analysis of the correlation between iron and hepcidin concentration showed a positive tendency in H63D carriers, while the wild type group showed a negative tendency at the basal and post-exercise point. Conclusions: ‪This study demonstrates that exercise has a distinct impact on iron metabolism through the hepcidin pathway with regard to the HFE gene status.